1995
DOI: 10.1103/physreva.51.r9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Mo/ller interaction on electron-impact ionization of high-Zhydrogenlike ions

Abstract: We have investigated the effects of the Mdller interaction in relativistic distorted-wave calculations of cross sections for electron-impact ionization of high-Z hydrogenlike ions. We found that the M611er interaction significantly increases the cross section for hydrogenlike uranium, and brings our calculated results into very good agreement with experimental results reported by Marrs, Elliott, and Knapp [Phys. Rev. Lett. 72, 4082 (1994)].We found similar increases in the cross sections for other hydrogenli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 4 publications
(9 reference statements)
4
26
0
Order By: Relevance
“…In particular, at 198 keV ͑t = 1.744͒, the experimental cross section of the former is 9.7 b, which compares very high relative to the value 2.82± 0.35 b of Ref. [51] and 2.88 b, the result estimated by Moore and Reed [52] from the cross section for U 91+ . The experimental value of Ref.…”
Section: K Ionization Of U 90+supporting
confidence: 45%
“…In particular, at 198 keV ͑t = 1.744͒, the experimental cross section of the former is 9.7 b, which compares very high relative to the value 2.82± 0.35 b of Ref. [51] and 2.88 b, the result estimated by Moore and Reed [52] from the cross section for U 91+ . The experimental value of Ref.…”
Section: K Ionization Of U 90+supporting
confidence: 45%
“…In particular, at 198 keV ( t = 1.744), the experimental cross section of the former is 9.7 barns, which compares very high relative to the value 2.82 ± 0.35 barns of Ref. 48 and 2.88 barns, the result estimated by Moore and Reed 53 from the cross section for U 91+ . The experimental value of Ref.…”
Section: Resultsmentioning
confidence: 42%
“…For example, this was necessary in the polarization of x rays emitted during electron-impact excitation of highly charged ions [1,2], dielectronic and radiative recombination effects [3][4][5], electron-impact-ionization experiments [6][7][8], and electron-and proton-impact excitation experiments [9]. For electron-impact excitation of highly charged hydrogenlike ions, Walker [10], Fontes et al [11], and Moores and Pindzola [12] have demonstrated that the Møller interaction or GBI can increase electron-impact-excitation cross sections by up to 50% in comparison to calculations that employ only the Coulomb interaction.…”
Section: Introductionmentioning
confidence: 99%